从流传和演变角度探析民间童话故事《虎姑婆》的教育意义 = An investigation of the transmission and educational implication of the folk tale “Aunt Tiger” - 黄思蓉 Wong, Sirong (2012)
《虎姑婆》类型故事在中国大陆以及台湾地区广泛流传。《虎姑婆》的故事原型始于中国大陆，出自清代黄之隽笔下的《虎媪传》，之后流传到各个地区而产生出类似的故事名称，例如《狼外婆》、《熊外婆》、《老虎外婆》、《老虎妈子》等等，而传到了台湾地区则被称为《虎姑婆》。本文将归纳前人的研究成果，列出《虎姑婆》故事的各种类型，从而对台湾地区和大陆地区《虎姑婆》类型故事进行比较分析。 这个典型的民间童话故事具有丰富的教育意义，透过生动有趣的故事情节，激发儿童的想象力、教导儿童如何辨别善恶、最重要的是赋予儿童一种“危机处理意识”，让他们在阅读这个故事之后思考如何在遇到危险或困难时勇敢地面对。笔者将此论文的焦点放在《虎姑婆》类型故事的教育意义。从这个故事的流传和演变过程中，探讨它正面以及负面的影响。The “Aunt Tiger” story is a popular folklore fairy tale widely circulated in China and Taiwan. This Chinese folk tale was first written down as text by Huang Zhijuan during the Qing dynasty, though it may have been in existence long before its written form. The story was circulated to different areas in China and Taiwan, and as time went by, the title of the story took different forms such as “Grandma Fox”, “Grandma Bear”, “Grandma Tiger”, and “Mother Tiger”. My main goal in this thesis is to compare the story patterns of the same story that appeared in China and Taiwan. My study will scrutinize the research findings by previous academics, and discuss how the same story has changed through time in different cultural environment. I will also discuss the educational significance of the “Aunt Tiger” folk tale. It is important to note that this tale has been one of the most familiar bed time stories to many Chinese children. The plot stimulates the children’s imagination, teaches them how to distinguish good and evil, and most importantly, demonstrates the ways to handle crisis. Besides the positive features of this story and the role it plays in children’s education, I will also investigate its negative influences, and how different adaptations emerged to avoid unfavorable elements in the story.